Toward carbon-aware networking - Zilberman, N; Schooler, EM; Cummings, U; Manohar, R; Nafus, D; Soulé, R; Taylor, R (Center for Networked Systems, UC San Diego, 2022)
Data transmission tends to be neglected when considering the carbon efficiency of systems, even though the electricity usage of data networks as a whole is as large, or larger, than that of data centers. Accounting for carbon cost of the movement of data is hard, and is often assumed to be the responsibility of the receiver or an intermediate provider.